ANALISIS ASSESMENT HIGHER ORDER THINKING SKILLS PADA MATERI IPA KELAS TINGGI SD N BUGANGAN 02 SEMARANG - Esti Devi Pratiwi; Filia Prima Atharina; Henry Januar Saputra (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2020)
Learners find it difficult to learn if asked to solve problems with high-level thinking (HOTS). Difficulties experienced by students are difficulties in working on HOTS-based question in which students are asked to think critically and understand the purpose of the questions be worked on. Descriptive qualitative research methods. Sources of research data are students in class V SD N Bugangan 02 Semarang. Data collection procedures used are observation, interviews, and documentation. The results showed that fifth grade students found it difficult to work on HOTS-based questions because in the learning process teachers rarely gave HOTS-based question so students were not accustomed to solving questions by thinking highly.